The Politics of God : Christian Theologies and Social Justice, Thirtieth Anniversary Edition - Tanner, Kathryn, 1957- (Book collections on Project MUSE., 2022)
This anniversary edition of The Politics of God includes a major new preface, in which Tanner addresses the changes in the social and political situation that have accumulated in the decades since the book's publication and resituates her argument for a new generation of theologians and activists.